PEPDar: a randomized prospective noninferiority study of ritonavir-boosted darunavir for HIV post-exposure prophylaxis - Fätkenheuer, Gerd; Vogelmann, Roger (HIV medicine, 2016)
Objectives PEPDar compared the tolerability and safety of ritonavir-boosted darunavir (DRV/r)-based post-exposure prophylaxis (PEP) with the tolerability and safety of standard of care (SOC). The primary endpoint was the early discontinuation rate among the per-protocol population. Methods PEPDar was an open-label, randomized, multicentre, prospective, noninferiority safety study. Subjects were stratified by type of event (occupational vs. nonoccupational, i.e. sexual) and were randomized to receive DRV/r plus two nucleoside reverse transcriptase inhibitors (NRTIs) or SOC PEP. Twenty-two private or university HIV clinics in Germany participated. Subjects were ≥ 18 years old and had documented or potential HIV exposure and indication for HIV PEP. They initiated PEP not later than 72 h after the event and were HIV negative. Results A total of 324 subjects were screened, the per-protocol population was 305, and 273 subjects completed the study. One hundred and fifty-five subjects received DRV/r-based PEP and 150 subjects received ritonavir-boosted lopinavir (LPV/r)-based PEP for 28-30 days; 298 subjects also received tenofovir/emtricitabine. The early discontinuation rate in the DRV/r arm was 6.5% compared with 10.0% in the SOC arm (P = 0.243). Adverse drug reactions (ADRs) were reported in 68% of DRV/r subjects and 75% of SOC subjects (P = 0.169). Fewer DRV/r subjects (16.1%) had at least one grade 2 or 3 ADR compared with SOC subjects (29.3%) (P = 0.006). All grades of diarrhoea, nausea, and sleep disorders were significantly less frequent with DRV/r, while headache was significantly more frequent. No HIV seroconversion was reported during follow-up. Conclusions Noninferiority of DRV/r to SOC was demonstrated. DRV/r should be included as a standard component of recommended regimens in PEP guidelines.